PENAKSIR RASIO REGRESI MENGGUNAKAN KOEFISIEN KURTOSIS DAN KOEFISIEN VARIASI UNTUK RATA-RATA POPULASI - Endah Dwi Jayanti; Arisman Adnan; Sigit Sugiarto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This paper  studies  three regression ratio estimators  for  population mean Y of the variable  Y  using information on two auxiliary variables  X  dan  Z  under simple random sampling without replacements.  This discussion is  a review  from the article of Singh  et al.  [Statistics  in Transition  10(1): 85-100].    All estimators are biased. The efficient estimator is  the  one with the  minimum  Mean Square Error (MSE), determined by comparing each type of the estimators.